Biohydrogen Production From Palm Oil Mill Effluent by Anaerobic Fermentation - Ahmed Yassin, Atif Abdelmoneim (2005)
Biological hydrogen production was investigated using biomass in palm oil mill effluent (POME) and artificial wastewater containing 1% glucose, 0.2% yeast extract and 0.018% magnesium chloride hexahydrate under anaerobic fermentation in a batch process. Activated POME sludge and different types of composts were collected as sources of inocula for the study. The anaerobic microflora were found to produce significant amounts of hydrogen. In the study with artificial media, 500 ml batch bioreactor was used. The experiments were carried out without pH control and at different temperatures. The maximum yield of 108.4 mmol-Hz/L-med (2.01 mol- H2/mol-glucose) at the maximum evolution rate of 182 rnl/(L-med hr) was obtained with Crest compost at 400C. Hydrogen production from POME was studied using a 5-L bioreactor optimal hydrogen production was observed at 600C and a pH range of 5.5 to 6.0, the maximal hydrogen yields of 179 mrnol/L-POME and 189 rnmol/LPOME at evolution rates of 454 ml/(L-POME hr) and 421 rnl/(L-POME hr) were obtained respectively. Fed batch hydrogen production was conducted to study the reproducibility of microflora for hydrogen production from POME. Two liters of reaction medium was removed and 2 liters of fresh POME was added to the reaction medium every 24 hr (15 times) and the reproducibility of the fed batch process was checked by changing feeding time every 8 hr (10 times). A yield of 2382 1x11-Hz/ L-POME and 2419 rnl-Hz/ L-POME at maximum evolution rates of 313 ml-Hz/ (L-POME hr) and 436 ml-Hz/(L-POME hr) were obtained respectively. Moreover, when the hydrogen production from POME using rnicroflora was scaled-up to 10 L bioreactor, hydrogen yields of 140 mrnol/LPOME and 96 mrnol/L-POME at evolution rates of 361ml/(L-POME hr) and 188 ml/(L-POME hr) were obtained at pH of 5.5 and uncontrolled pH respectively. Overall, hydrogen production was accompanied with the formation of acetate and butyrate. The experimental results showed that the gas composition contained hydrogen (66-68%) and carbon dioxide (32-34%). Throughout the study, methane gas was not observed in the evolved gas mixture. It was also found that the addition of nitrogen source in the medium caused a change in the hydrogen yield.A simple model developed from Gompertz Equation was applied to estimate the hydrogen production potential (P), hydrogen production rate (R,) and lag phase time (A), based on the cumulative hydrogen production curve. This study suggests that POME is suitable for biohydrogen synthesis without addition of any other nutrients. The finding of this study was highly reliable and showed that POME has potential for biological hydrogen production.